Implementation Of Education Quality Assurance (PMP) In The Context Of Improving PAI Learning Performance - Umi Henik (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
This study aims to describe the implementation of education quality assurance in improving PAI learning at MA At-tadzkir Kaliaren Grobogan. This research uses a type of descriptive qualitative research. Data collection techniques using interviews, observations, and document reviews. While data analysis is used, interactive analysis models include data reduction, data delivery, and conclusions. Based on the results of the study, the quality mapping carried out by the madrasah to improve PAI learning, in general, has been carried out well. The preparation of quality fulfillment plans carried out by the madrasah is quite good. The implementation of quality fulfillment carried out by madrasah to improve PAI learning is quite good, meaning that 8 national standards of education have been fulfilled in the implementation of madrasah, namely fulfillment of content standards, fulfillment of process standards, fulfillment of graduate competency standards, fulfillment of standards of educators and educational personnel, fulfillment of standards of facilities and infrastructure, fulfillment of management standards, fulfillment of financing standards and fulfillment of educational assessment standards.  The quality evaluation/audit conducted by the madrasah to improve PAI learning is quite good, shown by the implementation of formative evaluation referring to process indicators, summative evaluation referring to indicators of output, outcome, and impact, and auditing the SNP fulfillment process according to a previously set plan